EFFECTS OF TANNIN COMPOUNDS ON 2 SPECIES OF COLLEMBOLA - POINSOTBALAGUER, N; RACON, L; SADAKA, N; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
The effects of condensed and hydrolysable tannin extracted from evergreen oak leaves (Quercus ilex L.) were tested on two species of Collembola. Concentrations lower than those present in the litter leaves were toxic to these insects. Detoxification by washing with rainwater and biodegradation of tannic compounds are necessary for litter decomposition, in which microarthropods participated, to occur.
Citation
Keywords: Collembola; evergreen oak; Tannins

Determination of amino acids from the leaves of evergreen oak (Quercus ilex L.) at four different stages of decomposition - SADAKA, N; Poinsot-Balaguer, N (Biology and fertility of soils, 1987)
It was established by weak ion exchange resin chromatography that 17 amino acids in proteins and 15 free amino acids account for almost all of the amino acids present in the leaves of evergreen oak (Quercus ilex L.) in four different stages of decompo- sition. No significant change in the amounts of these amino acids was observed in the course of decomposi- tion. The amino acid content of evergreen oak leaves is comparable to that in pine needles and beech leaves.
Keywords: amino acids; Evergreen oak leaves; Quercus ilex L.; Stages of decomposition